2003
DOI: 10.1161/01.cir.0000058752.79734.f0
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation of Cardiac K + Channel Gene Expression

Abstract: Background— Many cardiac arrhythmias have their own characteristic circadian variations. Because the expression of many genes, including clock genes, is regulated variably during a day, circadian variations of ion channel gene expression, if any, could contribute to the fluctuating alterations of cardiac electrophysiological characteristics and subsequent arrhythmogenesis. Methods and Results— To examine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 40 publications
1
68
0
1
Order By: Relevance
“…Images of a Z-series were combined into a single image using the software program (Scanware, Leica). [10][11][12][13][14][15][16][17][18][19][20] were seeded onto glass coverslips (4 mm in diameter), coated with poly-L-lysine (Biochrome, Berlin, Germany) and were used after 3-5 days of incubation. The coverslip was placed into a perfusion chamber …”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Images of a Z-series were combined into a single image using the software program (Scanware, Leica). [10][11][12][13][14][15][16][17][18][19][20] were seeded onto glass coverslips (4 mm in diameter), coated with poly-L-lysine (Biochrome, Berlin, Germany) and were used after 3-5 days of incubation. The coverslip was placed into a perfusion chamber …”
Section: Immunohistochemistrymentioning
confidence: 99%
“…According to Itri et al [10], potassium channels are likely candidates to couple clock-related gene expression to membrane excitability, and thus also to secretion phenomena. Kv3.1b and Kv3.2 in the hypothalamic nucleus suprachiasmaticus (SCN) [10], Kv1.5 and Kv4.2 in heart [11] and the calcium-activated potassium channel Kcnma1 in the SCN [12] reportedly vary in expression levels in a circadian manner. Finally, the ether-a-go-go-related gene channel Erg1 (Kcnh2) was listed as being circadianly expressed in heart by Storch et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, this may also be regulated intrinsically by ion channels in the heart that influence myofilament activation 156,157 some of which exhibit diurnal variation. Time-of day dependent oscillations have been reported in the heart for the voltage dependent potassium channels K v 1.5 and K v 4.2 158 , and the L-type voltage-gated calcium channel subunit VGCCα1D. 159 Also, L-type calcium channel current densities increase during the active period which is consistent with the nocturnal elevation in murine heart rate.…”
Section: Iii) Circadian Mechanism and Cardiac Electrophysiologymentioning
confidence: 55%
“…This study revealed that two voltage gated K + (K v ) channels, 1.5 and 4.2, exhibit marked circadian rhythms, K v 1.5 peaking during the night and 4.2 during the day (at both mRNA and protein levels). Circadian oscillations of these K + channels correlated with diurnal variations in the electrical properties of isolated papillary muscles, suggesting functional alterations [91].…”
Section: Potential Indirect Regulation Of Myocardial Metabolism By Thmentioning
confidence: 93%
“…Ventricular tachyarrhythmias occur with a greater incidence in the daytime compared to the night [86][87][88], while atrial fibrillation is antiphase, peaking during the night [89,90]. Yamashita et al [91] have suggested that fluctuations in arrythmias may not only be caused by autonomic stimulation, but possibly by differential expression of K + channels within cardiomyocytes, in a time of day dependent manner. This study revealed that two voltage gated K + (K v ) channels, 1.5 and 4.2, exhibit marked circadian rhythms, K v 1.5 peaking during the night and 4.2 during the day (at both mRNA and protein levels).…”
Section: Potential Indirect Regulation Of Myocardial Metabolism By Thmentioning
confidence: 99%